2021
DOI: 10.1155/2021/4762027
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa Challenge Test Predicts STN-DBS Outcomes in Various Parkinson’s Disease Motor Subtypes: A More Accurate Judgment

Abstract: Background. The relationship between the levodopa challenge test (LDCT) and postoperative subthalamic nucleus-deep brain stimulation (STN-DBS) benefits is controversial in patients with Parkinson’s disease (PD). We aim to evaluate the value of total levodopa response (TLR) and symptom levodopa response (SLR) in predicting postoperative improvement in different PD motor subtypes. Methods. Studies were split into a training set (147 patients) and a validation set (304 patients). We retrospectively collected data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In this regard, the LCT is thought to provide an estimate of the maximum bene t a patient is likely to experience from STN stimulation. The cutoff criterion for the LCT has been found to vary considerably, and patient strati cation according to this measure can be unreliable [41][42][43]. An unexpected nding in this study was the correlation seen at both sites between stimulation-mediated outcomes and STN StimNet expression recorded in the baseline OFF condition.…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, the LCT is thought to provide an estimate of the maximum bene t a patient is likely to experience from STN stimulation. The cutoff criterion for the LCT has been found to vary considerably, and patient strati cation according to this measure can be unreliable [41][42][43]. An unexpected nding in this study was the correlation seen at both sites between stimulation-mediated outcomes and STN StimNet expression recorded in the baseline OFF condition.…”
Section: Discussionmentioning
confidence: 76%
“…It was reported that patients with a motor symptom improvement rate of <30% in the l-dopa impact test responded well to DBS (Zheng et al, 2021); and at our center, DBS was effective in some patients with <33% improvement in the LCT. As the LCT does not fully reflect brain function, it is important to establish other methods for predicting the response of PD patients to DBS.…”
Section: Introductionmentioning
confidence: 62%
“…A 30% or 33% improvement in Unified Parkinson’s Disease Rating Scale (UPDRS)-III score in the LCT has been set as a threshold for selecting candidates for DBS ( Defer et al, 1999 ); however, it is unclear how this can predict the effectiveness of the DBS operation. It was reported that patients with a motor symptom improvement rate of <30% in the l -dopa impact test responded well to DBS ( Zheng et al, 2021 ); and at our center, DBS was effective in some patients with <33% improvement in the LCT. As the LCT does not fully reflect brain function, it is important to establish other methods for predicting the response of PD patients to DBS.…”
Section: Introductionmentioning
confidence: 64%
“…Although the predictive value of the levodopa challenge score on parkinsonian symptoms control with DBS implantation is well documented ( 13 ) it was unclear whether the patient would benefit from the procedure given his mixed rest and action-postural tremor alongside a poor levodopa challenge score. Focusing on the limiting tremor symptoms impacting his dominant hand, meaningful improvements were achieved.…”
Section: Discussionmentioning
confidence: 99%